Verbal and Non-verbal Realizations of Persuasive Strategies in Video Resumes - MARIA ANGELES MESTRE-SEGARRA (Miscelánea: A Journal of English and American Studies)
With the rapid shift from print to digital modes of communication, new genres have emerged. One example is the video resume (VR). This novel professional digital genre enables job seekers to enhance their visibility and connect with broader audiences through various semiotic modes. The VR has a clear communicative aim based on a strong persuasive component: to secure a job by convincing the audience of their qualities. The premise of this paper is that VRs are not only informative but also inherently persuasive. Accordingly, the study aim is to explore the use of multimodal semiotic modes as a way of realizing persuasive strategies (i.e. attention-getting, anticipation and control of responses, rapport, emphasis and processing aids). The methodological approach uses video-based analysis and computer-aided multimodal discourse analysis (MDA) to analyze a dataset of 8 VRs from the online platform YouTube, considering the following criteria: limited duration, impact, year uploaded and editing. The results suggest that verbal and non-verbal realizations of persuasive strategies are present in the fragments analyzed, and such strategies are encoded by heterogeneous combinations of semiotic modes. Although the strategies and modes are not always consistent, they contribute to achieving the communicative purpose of the genre. As for pedagogical implications, this genre and its features can be incorporated into English for Specific Purposes (ESP) teaching materials, enhancing learners’ persuasive strategies and developing their multimodal communicative competence.